Evaluation of Limb Muscle Strength and Function in People With Chronic Obstructive Pulmonary Disease. Issue 1 (January 2019) - Mathur, Sunita; Dechman, Gail; Bui, Kim-Ly; Camp, Pat G.; Saey, Didier
Abstract : Purpose: Muscle weakness is an observable consequence of limb muscle dysfunction in people with chronic obstructive pulmonary disease (COPD). The purpose of this review is to describe clinically applicable methods of muscle strength testing and functional tests that are associated with muscle strength in people with COPD. Summary of Key Points: Several tests and devices for evaluating muscle strength have been described in COPD. Isometric quadriceps strength testing, which is associated with clinical outcomes in COPD, can be reliably tested using fixed dynamometers or strain gauges in clinical and laboratory settings. Functional tests that are correlated with muscle strength in COPD include the Stair Climb Power Test, Sit-to-Stand test, and Timed Up and Go test. These tests are easy to conduct in the clinical setting and are relevant to daily activities; however, performance depends on factors such as balance and coordination in addition to leg muscle strength. Conclusions: Muscle strength assessment should be considered an integral part of the evaluation of people with COPD. Clinicians and researchers can select from a variety of valid and reliable tests to evaluate muscle strength based on their available resources and goals of the patient.